LIFETIME AND PRODUCTION-RATE OF BEAUTY BARYONS FROM Z-DECAYS - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Allport, P; Almehed, S; Alvsvaag, S; Amaldi, U; Amato, S; et al. (1995)
The production and decay of beauty baryons (b-baryons) have been studied using 1.7×106 Z hadronic decays collected by the DELPHI detector at LEP. Three different techniques were used to identify the b-baryons. The first method used pairs of a Λ and a lepton to tag the b-baryon decay. The second method associated fully reconstructed ΛC baryons with leptons. The third analysis reconstructed the b-baryon decay points by forming secondary vertices from identified protons and muons of opposite sign. Using these methods the following production rates were measured:[Figure not available: see fulltext.] The average b-baryon lifetime was determined to be:[Figure not available: see fulltext.] © 1995 Springer-Verlag.